Translation Strategies of American Teenagers’ Slang: A Descriptive Analysis - Suminar, Ratna Prasasti (Universitas Pendidikan Mandalika, 2024)
This research is about the analysis of the American teenagers’ slang translation strategies in Easy A movie subtitles based on Gottlieb’s theory. Translation is seen as important aspect in helping the target communicant understand the content and messages of the utterance. Besides, slangs, though hardly ever discussed in classroom setting, are commonly used in social context, and in movies. Easy A is a movie talking about school life which is close to students’ daily activities. This research aims to know the English slangs appeared in Easy A movie, the strategies the translator uses in translating his or her subtitles of the slang expressions from the English language as the source language (SL) to the Indonesian language as the target language (TL), and the most strategies used.. In this study, the researcher uses a qualitative method to analyse the data. The slang expressions are analysed by selecting and marking the utterances and text containing slang expressions. To support the research, the researcher uses some online dictionaries to determine if the slang is originally from America and to find each slang meaning. The result of this research shows, there are seven strategies used by the translator or subtitle in translating slang expressions: Expansion, Paraphrase, Transfer, Imitation, Condensation, Decimation, and Deletion. Three strategies are not found. They are Transcription, Dislocation, and Resignation strategy. Based on this result, the most often used by the translator is Transfer strategy. It is because the translator translated every slang expression completely. Paraphrase strategy is in second place. It indicates that the translator attempts to make the slang expressions easier to be understood by the audience.